THE EPISTEMOLOGICAL STRUCTURE OF TAFSIR IQTISADI (THE STUDY OF AT-TAFSIR AL-IQTISADI LI AL-QUR’AN AL-KARIM BY RAFIQ YUNUS AL-MASRI - Didin Baharuddin; Hamdani Anwar; Euis Amalia (Al-Bayan: Jurnal Studi Al-Qur'an dan Tafsir, 2021)
This article discusses the epistemological structure of At-Tafsīr al-Iqtiṣādī li al-Qur'ān al-Karīm by Rafīq Yūnus al-Maṣrī. The author of this tafseer is an economist, a researcher at the Center for Islamic Economic Studies University of Malik 'Abdul' Azīz, and is active in Al-Jam'iyah Ad-Dauliyah li Al-Iqtisād London. The author's background makes this book very interesting to study because not many economists have written tafsir studies. This article is a literature study employing a descriptive-analysis method and a historical-philosophical approach. This study shows that the interpretation of At-Tafsīr al-Iqtiṣādī li al-Qur'ān al-Karīm was written in a tartib mushafi model, and predominantly used tafsīr bi ar-ra'yi with the nuances of the tafsīr iqtiṣādī. The nuances of the iqtiṣādī interpretation come from tafsīr ʻilmī, which shows scientific theories from the Qur’an. Through the tafsīr iqtiṣādī, Rafīq Yūnus al-Maṣrī attempted to show that the Qur’an can be interpreted using an economic approach and argued that the Qur’an provides the existence of economic theories. Among these theories are Musykilah an-Nadirah an-Nisbiyah (relative scarcity), at-Tafḍīl az-Zamanī (time preference), and Ta’dzīm al-manāfi’ (profit maximisation).